Analisis Kesiapan Implementasi Rekam Medis Elektronik Rawat Jalan di Rumah Sakit X - Nafis, Muhammad; Poernareksa, Dwidya; Rosyadi, Muhammad Dedy; Khairunnisa, Khairunnisa (HB PRESS, 2024)
Changing the medical record information system from manual to electronic will make it easier to record information about patients in a practical and fast way. This change is related to the Regulation of the Minister of Health of the Republic of Indonesia, namely that all health facilities are expected to have implemented electronic medical records in accordance with the provisions no later than December 31, 2023. In this case, it is necessary to know the level of readiness of hospitals in implementing outpatient electronic medical records. The purpose of this study was to analyze to determine the readiness of implementing outpatient electronic medical records at Hospital X using the Doctor's Office Quality – Information Technology (DOQ-IT) method. The type of research used is descriptive quantitative. The research instrument is a questionnaire. Readiness analysis using the EHR Readiness Starter Assessment from DOQ-IT. The level of readiness for the implementation of outpatient electronic medical records at Tk. III Dr. R. Soeharsono Banjarmasin is very well prepared. This value is included in the very ready score range. While the level of readiness for implementation in the variable, namely, organizational work culture of 42.14 is in the very ready score range, 34.72 leadership governance is in the very ready score range, human resources is 21.19 in the very ready score range, and IT infrastructure of 15.69 is in the fairly ready range of scores.